(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This academic article explores the role of the Uzbek and English languages as national-cultural values within the conceptual sphere of "Generosity." It delves into the cultural significance of language and its impact on fostering generosity in Uzbek and the global community. By examining the linguistic resources, communication patterns, and cultural practices associated with both languages, we uncover their contributions to the expression and promotion of generosity within their respective contexts. This article sheds light on how language serves as a bridge for understanding, empathy, and acts of kindness, ultimately fostering a culture of generosity